2020
DOI: 10.3390/w12092381
|View full text |Cite
|
Sign up to set email alerts
|

A Biosorption-Pyrolysis Process for Removal of Pb from Aqueous Solution and Subsequent Immobilization of Pb in the Char

Abstract: The application of biosorption in the removal of heavy metals from water faces a challenge of safe disposal of contaminated biomass. In this study, a potential solution for this problem was proposed by using a biosorption-pyrolysis process featured by pretreatment of biomass with phosphoric acid (PA). The PA pretreatment of biomass increased the removal efficiency of heavy metal Pb from water by sorption, and subsequent pyrolysis helped immobilize Pb in the residual char. The results indicate that most (>95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The fundamental base is leaching the contaminated plant biomass with acids to recover the adsorbed metal and to obtain biomass with metal concentrations in the range of environmental norms. Wang et al [57] combined this concept and found that acid treatments improved plant biomass to adsorb more metals and can be further used to prepare biochar by pyrolysis aimed to confine metals.…”
Section: Phytominingmentioning
confidence: 99%
“…The fundamental base is leaching the contaminated plant biomass with acids to recover the adsorbed metal and to obtain biomass with metal concentrations in the range of environmental norms. Wang et al [57] combined this concept and found that acid treatments improved plant biomass to adsorb more metals and can be further used to prepare biochar by pyrolysis aimed to confine metals.…”
Section: Phytominingmentioning
confidence: 99%
“…Pb(II) is hard to migrate and degrade, which have become an important cause of Pb(II) pollution in soil, water, air, and many other places. [5][6][7][8][9][10][11][12][13] Lead (II) exists in the environment will eventually be transmitted to plants and the human body through the food chain, [14][15][16][17][18][19] causing damage to organs [20] and hormone levels. [21] For children, a very small amount of Pb(II) may inhibit their brain development, [22] break their bones, [23] even damage their DNA.…”
Section: Introductionmentioning
confidence: 99%